Interleukin-27 Functional Duality Balances Leishmania Infectivity and Pathogenesis - Jafarzadeh, Abdollah; Nemati, Maryam; Chauhan, Prashant; Patidar, Ashok; Sarkar, Arup; Sharifi, Iraj; Saha, Bhaskar (Frontiers in Immunology, 2020)
IL-27 is a unique cytokine that exerts diverse effects on the cells of innate and adaptive immune systems. IL-27 is chiefly expressed in macrophages and dendritic cells during the early phase of Leishmania infection. IL-27 contributes to the protection against L. major infection. However, it suppresses the protective Th1 response against L. donovani, L. infantum, L. amazonensis, and L. braziliensis infection, suggesting a functional duality in the cytokine. During the late stage of Leishmania infection, IL-27 limits the immunopathogenic reactions and tissue damages. Herein, we analyze the mechanism of the functional duality of IL-27 in the resistance or susceptibility to Leishmania infection, prompting IL-27 for anti-leishmanial therapy.